1996
DOI: 10.1002/(sici)1099-1573(199608)10:5<383::aid-ptr855>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Inhibition by Allicin, the Molluscicidal Agent ofAllium sativumL. (Garlic)

Abstract: Allicin, a molluscicidal component of garlic inhibited the activity of acetylcholinesterase, lactic dehydrogenase and alkaline phosphatase in in vivo and in vitro exposure against Lymnaea acuminata. It was observed that succinic dehydrogenase activity in the nervous tissue of Lymnaea acuminata was increased in in vivo treatment whereas with in vitro exposure, allicin caused no significant change in succinic dehydrogenase activity. The inhibition kinetics of these enzymes indicates that allicin caused an uncomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Toxicity of nutmeg and mace extracts against L. acuminata is in the range of high molluscicidal activity, the LC 50 value being less than 100 mgL −1 (24,25). Thus, the 96-hour LC 50 of column-purified fraction of nutmeg (3.98 mgL −1 ) and mace (2.77 mgL −1 ) against L. acuminata are lower than those of 96-hour LC 50 values of synthetic molluscicides.…”
Section: Discussionmentioning
confidence: 93%
“…Toxicity of nutmeg and mace extracts against L. acuminata is in the range of high molluscicidal activity, the LC 50 value being less than 100 mgL −1 (24,25). Thus, the 96-hour LC 50 of column-purified fraction of nutmeg (3.98 mgL −1 ) and mace (2.77 mgL −1 ) against L. acuminata are lower than those of 96-hour LC 50 values of synthetic molluscicides.…”
Section: Discussionmentioning
confidence: 93%
“…However, SDH activity was not altered significantly. Singh and Singh27 have reported that allicin is an uncompetitive inhibitor of AChE and a competitive inhibitor of LDH and alkaline phosphatase in the nervous tissue of L acuminata . It seems that the higher inhibition (as evident from SR values) of AChE, LDH and alkaline phosphatase activity in nervous tissue of snails exposed to allicin + PB or ENT 8184 may be due to the inhibition of certain enzymes which detoxify allicin in the snail.…”
Section: Discussionmentioning
confidence: 99%
“…nerve synapses, so that the post synaptic membrane is in the state of permanent stimulation causing paralysis, ataxia, convulsion and death of animal. 23,24,35 T. indica seed extract caused dose dependent inhibition of phaspholipase A and other enzyme activity of snake venom. 25 Zhanq et al 26 reported the in vitro cytotoxic effect of procynadine on human hepatoma G2 cell.…”
Section: In Vitro Enzyme Inhibitionmentioning
confidence: 97%